Isolation and Characterization of a Slowly Milk-Coagulating Variant of Lactobacillus helveticus Deficient in Purine Biosynthesis - Hebert, Elvira Maria (2001)
A slowly milk-coagulating variant (Fmc-) of Lactobacillus helveticus CRL 1062, designated S1, was isolated and characterized. Strain S1 possessed all the known essential components required to utilize casein as a nitrogen source, which include functional proteinase and peptidase activities as well as functional amino acid, di- and tripeptide, and oligopeptide transport systems. The amino acid requirements of strain S1 were similar to those of the parental strain. However, on a purine-free, chemically defined medium, the growth rate of the Fmc- strain was threefold lower than that of the wild-type strain. L. helveticus S1 was found to be defective in IMP dehydrogenase activity and therefore was deficient in the ability to synthesize XMP and GMP. This conclusion was further supported by the observation that the addition of guanine or xanthine to milk, a substrate poor in purine compounds, restored the Fmc+ phenotype of L. helveticus S1.